THE STUDY ON CAPITAL STRUCTURE FUNDING STRATEGY AGAINST THE DEVELOPMENT OF FINANCIAL PERFORMANCE OF PUBLIC LISTED COMPANIES IN CHINA (American Journal of Business Management, Economics and Banking, 2023)
The purpose of the current study had been aimed to provide the insight on the relevance impact for the capital structure funding strategy of the business in affecting the development of the financial performance of the public listed companies in China mainly focusing on the companies listed in Shanghai Stock Exchange (SSE) and Shenzhen Stock Exchange (SZSE). The previous studies had revealed the potential expectations of the outcome in the quantitative study to observe ethe positive correlation and relationship from the capital structure financing against the financial performance of the business. Through the quantitative study method, the research framework had been translating into the statistical testing output which observe the data input of debt equity ratio as the representation of the capital structure as independent variables while the financial performance as the dependent variable for the study had been represented by the profitability ratios including the gross profit margin, net profit margin, return one equity and return on asset. The results for the research had identified only the return on equity is being impacted from the designation of the capital structure funding but not applicable for other variables. The outcome of the study had concluded major disagreement from the initial literature review which create a fresh insight inducing the potential future study to further explore the relevance focus on the scope of study into different environment and target population of the study using the similar research framework for the purpose of future research.